Starvation before slaughtering as a tool to keep freshness attributes in gilthead sea bream (Sparus aurata) - Ginés, R.; Palicio, M.; Zamorano, M. J.; Argüello, A.; López, J. L.; Afonso, J. M. (0967-6120, 2002)
Instrumental quality parameters related to freshness were evaluated for gilthead sea bream ( Sparus aurata) after different storage periods on ice ( 2, 4, 7 and 11 days of storage) for one, four and eight days of pre-slaughter starvation. The study was carried out on 360 gilthead sea bream from five different groups reared on a commercial fish farm. Starvation period had a significant effect on fish texture: the force necessary to compress 4 mm of flesh after two days ice storage in 1 day starved fish (16.50 +/- 0.59 Newtons) was less than that for four day ( 18.98 +/- 0.63 Newtons) and eight day starved fish (20.43 +/- 1.12 Newtons). Significant differences in flesh puncture and flesh compression were not detected, although these values did increase with increasing starvation period. A significant increase in pH and myofibrilar protein solubility was also detected for fish starved for one day. 389 379 0,301 Q4 SCIE